Training in women soccer players: A systematic review on training load monitoring - Costa, Júlio A.; Rago, Vincenzo; Brito, Pedro; Figueiredo, Pedro; Sousa, Ana; Abade, Eduardo; Brito, João (Frontiers in Psychology, 2022)
Objective The present systematic review aimed to provide an overview of training load (TL), along with their responses, monitoring during training sessions in highly trained and elite adult women soccer players. Data source Electronic databases searches (PubMed, Scopus, Web of Science and Ebsco) for relevant studies published in peer-reviewed journals were conducted, and eligibility criteria were based on the PICOS model in accordance with PRISMA guidelines. Study selection Studies were considered as follows: (a) highly trained and elite adult (>18 years) women’s soccer players; (b) continuous (minimum 1-week duration) TL monitoring in the context of the team routine; (c) TL collected from entire training session. Methodological qualitative assessments and risk of bias criteria were used for judging the studies. Data extraction A total of 1,163 studies were identified, and 16 were included. The selected studies were fully screened to extract the population characteristics; the number of players; a type of study design; region where the study was performed; the main findings. Data synthesis Accumulated external TL (ETL) during the pre-season was positively correlated to enhanced adaptations in intermittent exercise capacity. Daily ETL was negatively correlated to next-day self-reported fatigue and muscle soreness. Daily internal TL (ITL) was negatively correlated to post-session sleep duration and sleep efficiency. One study showed that higher accumulated player load and total distance were associated with injury. Conclusion Information about TL during training sessions in women soccer players is very sparse, and it is currently very difficult to consider evidence-based practices for training sessions in highly trained and elite adult women soccer players. Moreover, the dose–response relationships between TL and training outcome (e.g., fatigue, training adaptations and injuries) need to be further explored to understand the optimal training stimulus to enhance performance outcomes while preserving player health.